(3CNHGQ GdfMhjjfs - (3GdMSf Hf YHO Gddg Hf GdeQRHGf GdSjQGaj GdfMhj , CHh SYjO, J (B368 (3g` s
(3ChdgG (B:s
(3abGd bGFdhf CHh GdCShO GdODdi , hbGd BNQhf CdN s
(3BNQgG (B:s
(3hYdjgG bQCJ cJGH SjHhjg hai WHbGJgeG eef NdW Yde GdHUQjjf HYde Gdchajjf CHh HcQ He TbjO hGHh HcQ Hf GdNjGW s
(3GdfSNI ebGHdI heUMMIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B242s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B133 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe LRA (B2/ 1 - (3U (B8 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdJGQjNs